Evaluating the influence of climate change knowledge on intention towards pro-environmental behavior - Yeang Chan, Mee; Halim, Lilia; Mohamad Nasri, Nurfaradilla (International Journal of Evaluation and Research in Education (IJERE), 2025)
Pro-environmental behavior is essential for mitigating climate change, with climate change knowledge often considered a prerequisite for fostering intentions toward such behaviors. However, the specific types of climate change knowledge that most effectively promote pro-environmental behavior remain unclear, indicating a need for further investigation. This survey was conducted among 308 randomly selected Form Two students (average age 14) to respond to a questionnaire consisting of 24 items. The study aimed to explore the relationship between various types of climate change knowledge and students’ intention to engage in pro-environmental behavior. Using SPSS version 25.0 software, both descriptive and inferential analyses (correlation and multiple regression) were conducted. Findings revealed that students had the highest level of knowledge regarding mitigation actions, followed by knowledge of the causes and impacts of climate change respectively. All three types of knowledge were significantly and positively correlated with the intention to engage in pro-environmental behavior. Regression analysis showed that students’ knowledge on mitigation actions influence the most to the intention compared to the other types of climate change knowledge. The study recommends enhancing students’ understanding of the causes of climate change, which could, in turn, improve their knowledge of impacts and better guide their mitigation actions, ultimately fostering higher levels of pro-environmental behavior.